ALKYLARYLKETONE HOMOLOGOUS SERIES FOR DETERMINATION OF KOVATS RETENTION INDICES WITH RP-HPLC USING ACETONITRILE/WATER SYSTEM - Rinaldi Idroes (Universitas Gadjah Mada, 2010)
Some factors such as the changes of the stationary phase, temperature, pH-value, mobile-phase composition and flow rate play a crucial role in effecting the sensitivity of retention times in high performance liquid chromatography (HPLC) system. Utilizing a retention index system is one of the methods to minimize those effects. Besides the mentioned factors, dead-time influences on determining the retention index as well. In comparison with Gas Chromatography (GC), the retention Index determination method in HPLC is still widely discussed, due to the difficulty of utilizing n-alkane as standard. In addition, the solutes in HPLC interact with the mobile-phase, thus the retention behavior also depend on the mobile-phase. Actually, It is difficult to use n-alkanes in HPLC as standards in case of some considerable problems, due to they are very non polar but also large retention times which lack of chromophores. Therefore, using n-alkane in routine analysis could be inconvenient. In comparison with n-alkanes, the alkylarylketones homologous series are stable compounds, commercially available and easily detected by a UV detector. This paper introduces Determination of Kovats Retention Index in the HPLC using Alkylarylketone homologous series and then is connected with n-alkane as a frame of reference. Steroids were used as test substance for calculating Kovats retention index values in acetonitrile/water system.